Playing Checkers with Machines--from Ajeeb to Chinook. - Kidwell, Peggy Aldrich (Information & Culture, 2015)
Chess-playing automata that also played checkers were built in Europe from the late eighteenth century. One of these, named Ajeeb, came to the United States, spending much of the time from 1885 into the 1930s in New York and taking occasional tours around the country. The advent of electronic computers in the mid-1940s encouraged attempts to play games using machines in both Britain and the United States. By the late twentieth century, a Canadian-written computer program, Chinook, had defeated world champion and mathematician Marion Tinsley. More recently, developers of Chinook announced that checkers could be played to a draw against any opening.